Fetal ascites: Apropos of a case and literature review - H. Novoa, Rommy (2019)
Fetal ascites is defined as the presence of intraperitoneal fluid that may be part of a generalized or isolated hydrops. The mortality of non-immune ascites, both fetal and neonatal, is approximately 60%. We present a case of fetal ascites not associated with hydrops and we review the pathogenesis, clinical features, diagnostic approach and treatment of this fetal and neonatal condition.